Self-employment and the role of health insurance - Gulcin Gumus; Tracy L. Regan (Institute for the Study of Labor (IZA), 2009)
We investigate the effect of health insurance on labor market transitions in and out of self-employment as well as on the likelihood of being self-employed. We consider the role of individual health insurance coverage along with that from a spouse. Next, we examine a series of tax deductions granted to the self-employed through amendments made to the 1986 Tax Reform Act. Using data from the Current Population Survey for 1996-2007, we find significant but small effects of the after-tax health insurance premium on the entry rate, with no effect on exits from self-employment or the likelihood of being self-employed.
urn:nbn:de:101:1-20090209226
Keywords: J32; J48; I11; 330; Health insurance; self-employment; CPS; ORG; Krankenversicherung; Versicherungsschutz; Selbstständige; Steuerbegünstigung; USA